Konseptualisasi Public Value dalam Manajemen Pelayanan Publik di Era Digital - Mahmud, Magfira; Mozin, Sri Yulianti; umar, Marsela (Saraq Opat: Jurnal Administrasi Publik, 2025)
Digital transformation in the public sector drives a paradigm shift from a traditional administrative approach towards a model oriented on the creation of public value. The concept of public value becomes a strategic framework that emphasizes the importance of legitimacy, performance, and community support in public service management. This study aims to examine how public service management can be reconceptualized in the digital era with an orientation towards public value creation. The method used is a qualitative literature review of recent national and international journals, including case studies such as e-Government services in Indonesia (Kusudiandaru & Umanto, 2024) and public transportation system management (Celia & Andono, 2023). The study results indicate that the integration of information technology, value-based management control systems, and stakeholder engagement are the main prerequisites for sustainable public value creation. This study concludes that public value is not only measured through bureaucratic output but also through public perception, participation, and trust in the service-providing institutions